Implant- and tooth-supported removable partial dentures: a case report - MELO,Jéssyca Maria França de Oliveira (2020)
ABSTRACT This study aimed to report treatment of a patient with Kennedy’s class l maxillary and class II mandibular arch with removable partial dentures supported on an external hexagon (HE) anterior type implant of regular diameter fitted with an O’ring type of attachment. This clinical case reports the oral rehabilitation of a senile patient whose clinical examination revealed missing dentition in the upper and lower arches, attrition of the lower anterior teeth, caries, and motor impairment affecting hygiene, mastication, and esthetic functions. Due to few severely impaired teeth, the pre-prosthetic preparation included extractions and restorations, followed by the fabrication of upper and lower removable partial dentures supported by an HE-type implant. This study is important because it addresses the current challenges faced in the implementation of treatment involving removable partial dentures combined with implants, which is a topic that still needs long-term follow-up and research.